VD_FINDINFO Pron / 2012 / 130 vom 11. Juni 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, DÉPENS | 109 CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)